Data supporting: 'Assessing and mitigating the distortion and stress during electron beam welding of a large shell-flange structure' - Sun, Yongle; Smith, Mike; Dutilleul, Thomas; Jones, Steve (Cranfield University, 2022)
Fig. 7. (c) temperature histories on the outer surface points (i.e., Out1 and Out2) and inner surface points (i.e., In1 and In2). Fig. 8. (d) The cross-weld line profile of hardness distribution. Fig. l10. Evolution of the opening (a) and sliding (b) displacements for mid-thickness ocations on the weld plane with different angular distances to the EB weld start position.
Keywords: 'Fusion welding'; 'Weld restraint'; 'Nuclear Steel'; 'Distortion'; 'Transient stress'; 'Residual stress'; 'Modelling'